Students' attitudes toward books and computers. - Noyes, Jan; Garland, Kate (Computers in Human Behavior, 2005)
Many studies have compared paper and computers using objective performance measures. The aim of the study reported here was to extend this body of work by considering subjective measures. A questionnaire survey of 217 people showed that books were perceived more favorably than computers on all of the affective scales of Kay's Computer Attitude Measure (CAM; 1993). Further, respondents preferred to learn from books rather than computers, and expected to learn more from them than computer-based material. The conclusion reached is that people have a strong affection for books, prefer them to computers for learning purposes, and expect to learn more from them. Copyright (c) 2004 Elsevier Ltd